Association Between Community Environment and Depressive Symptoms Among Chinese Middle-aged and Older Adults: Evidence From National Longitudinal Surveys From 2011 to 2018. Issue 11 (6th February 2022) - Zhou, Ying; Wu, Qi; Li, Chenshuang; Ding, Lieyun
Abstract: Background: Despite the growing evidence on the relationship between community environment and depressive symptoms, little is known about the longitudinal relationship in older adults. This study aimed to examine the longitudinal association between community environment and depressive symptoms based on a nationally representative survey among Chinese middle-aged and older adults. Methods: A total of 6 872 participants from the latest four waves (2011, 2013, 2015, and 2018) of the China Health and Retirement Longitudinal Study were included. The Center for Epidemiologic Studies Depression Scale was used to measure depressive symptoms, and Cox proportional hazards regression models were conducted to investigate the longitudinal association between community environment and depressive symptoms after adjusting included covariates. Results: Both community infrastructure and organizations were significantly associated with depression, and infrastructure was associated with higher risk reduction in depression (hazard ratio [HR], 0.77; 95% confidence interval [CI], 0.66–0.89). Furthermore, we estimated the heterogeneous effects of community infrastructure and organizations for vulnerable populations. Additionally, family-based elder-care center (HR, 0.63; 95% CI, 0.46–0.86) and outdoor exercise facilities (HR, 0.76; 95% CI, 0.68–0.84) were found as significant correlates associated with lower depressive symptom risk. Conclusions: Our findings indicated that targeted and specific measures should be taken to improve the construction of community infrastructure and strengthen the role of community organizations. Specifically, providing a family-based elder-care center and establishing outdoor exercise facilities might be effective methods to reduce the risk of depression and relieve related public health burdens among Chinese middle-aged and older adults.